2008
DOI: 10.1002/mrd.20965
|View full text |Cite
|
Sign up to set email alerts
|

Acid peptidase activity released from in vitro produced porcine embryos: A candidate marker to predict developmental competence

Abstract: SUMMARYThe ability to efficiently create high quality embryos, competent to produce normal viable offspring in vitro, facilitates diverse technological advancements in animal agriculture and assisted reproduction. Current methods for evaluation of embryos are predominantly based on morphological characteristics which are prone to potential bias of the scorer. Metabolic and genetic markers have also been explored for quality assessment, but they are cost prohibitive or require longer periods of time for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…The function of PAG2 has not been elucidated. Normally, PAG2 has very high expression levels (174.4‐fold higher than the reference cDNA in this study) and also has measurable acid peptidase activity (Telugu and Green, 2008; Telugu et al, 2009), but in this study NT extraembryonic membranes showed a decrease in PAG2 transcript and protein expression and acid peptidase activity. The NT extraembryonic membranes in this study showed PAG2 protein accumulating at the microvillar junction by Day 35 and in one case PAG2 immunoreactivity was also present in the LE.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The function of PAG2 has not been elucidated. Normally, PAG2 has very high expression levels (174.4‐fold higher than the reference cDNA in this study) and also has measurable acid peptidase activity (Telugu and Green, 2008; Telugu et al, 2009), but in this study NT extraembryonic membranes showed a decrease in PAG2 transcript and protein expression and acid peptidase activity. The NT extraembryonic membranes in this study showed PAG2 protein accumulating at the microvillar junction by Day 35 and in one case PAG2 immunoreactivity was also present in the LE.…”
Section: Discussioncontrasting
confidence: 58%
“…The optimum pH for proteolytic activity of porcine PAG2 is 3.5 (Telugu and Green, 2008), therefore acid peptidase activity of extraembryonic membrane extracts was measured at this pH as described previously (Telugu et al, 2009) with minor modifications. Briefly, APA was measured in 40 µg protein lysates (the same lysates that were used for Western blotting analysis), each of the three biological replicates was measured in quadruplicate, resulting in 12 measurements/treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Subspecies genotype also affects plasma pregnancyassociated glycoprotein (PAG) concentrations during pregnancy. These proteins are part of a large family of aspartic proteases detected in the maternal circulation throughout most of pregnancy (Xie et al, 1997;Telugu et al, 2009;Pohler et al, 2016).…”
Section: Pregnancy Differences Between B Indicus and B Taurus Femalesmentioning
confidence: 99%
“…The function of PAG2 has not been elucidated. Normally PAG2 has very high expression levels in the placenta and also has measurable acid peptidase activity (Telugu and Green, 2008; Telugu et al, 2009). PAG2 message and protein were down‐regulated in SCNT placentas compared to in vivo placentas by more than four‐ and two‐fold, respectively (Fig.…”
Section: Effect Of Nuclear Reprogramming On Placental Developmentmentioning
confidence: 99%